A quantile regression analysis of price transmission in Thai rice markets - Aree Wiboonpongse (2018)
We analyze the price efficiency by investigating the backward and forward transmissions of prices from the wholesale markets for white rice to and from the farm level. We compare the price transmissions at different price levels. This study utilizes monthly price data at farm and wholesale markets of white rice during 1997 to 2012. The effect of the structural change due to the price insurance program is considered. The quantile cointegration regression model is used in the empirical analysis. The findings reveal the existence of asymmetry in most aspects of the price transmission of farm-white rice markets. In the backward transmission (from wholesale to farm), asymmetric adjustment did occur but at only low prices and it was in favor of farmers. Asymmetry persists in the price transmission in the forward direction (farm to wholesale markets) at all price levels. The price insurance program had statistically significant effects on elasticities of transmission at almost all price levels but their effects were numerically very small. As backward transmission is in favor of farmers, an appropriate credit program is strongly recommended to manage timely sale of paddy. © 2013 Springer-Verlag Berlin Heidelberg.